Effect of Recombinant Erythropoeitin in Anemia Due to Chronic Renal Failure - Husein Alatas; Fahrul W. Arbi; Taralan Tambunan; I.G.N. Wita Wirya (Paediatrica Indonesiana, 1997)
Recombinant human erythropoeitin (rHuEPO) was administered to 16 patients hospitalized at the Department of Child Health Faculty of Medicine University of Indonesia Cipto Mangunkusumo Hospital between July 1992 until December 1994, with anemia (Hb < 8 g dl) due to chronic renal failure (creatinine uclearance < 30 ml/min/1.3 mJ). three of them with end stage renal failure (creatinine clearance < 5 ml/min/1.73 nr). The average age was 15.9 years (range 4-16 years) the proportion of sex were the same. An initial dose of 150 lU/kgBW/week rHuEPO was administered subcutaneously. The dose was increased by 75 U/kgBW/week and maintained when the hemoglobin level reached 11 g/dl. Good result was mostly found at the dose of 150-199 IU/kgBW/week. The hemoglobin level rose from 6.79 + 1.19/dl before treatment to 10.4 + 3.9 g/dl after treaunent (p=0.011). Six cases failed to reach Hb 1 lg/dl, one of them with severe hypertension while in the other case had peritonitis. Decrease of the serum ferritin level during treatment indicated that ferrum was utilized for erythropoesis. This study showed that in chronic renal insufficiency we should consider to give r-HuEPO to increase hemoglobin to avoid giving recurrent blood tranfusion; however, the cost may limit its widespread use.